(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article investigates modern folk jokes about Muscovites. It emphasizes that the anecdote is considered to be one of the most productive and popular folk genres, easy changeable in terms of new life realities. This paper represents the fact that the complexity and ambiguity of the Muscovite folklore image, his national and social interpretation are considerably caused by historical, political, and psychological peculiarities of Ukrainian history.